Familias monoparentales y su relación con el desarrollo socio-afectivo de los niños y niñas de 4 a 5 años de edad del centro de desarrollo infantil “El Paraíso Mágico” de la ciudad de Loja periodo lectivo - Merino Veintimilla., Liliana Estefanía (2015)
This research titled PARENT FAMILIES AND THEIR RELATIONSHIP WITH SOCIO-EMOTIONAL DEVELOPMENT OF CHILDREN FROM 4 TO 5 YEARS OLD CHILD DEVELOPMENT CENTER "THE MAGIC PARADISE" CITY OF LOJA semester 2014 - 2015. It is structured based on the current Guidelines Graduation at the National University of Loja. The overall objective in this study was focused to: Analyze single parents and their relationship with socio-emotional development of children of 4-5 year old child development center "Magical Paradise" from the city of Loja. The methods used were: Scientific, Descriptive, analytic-synthetic, inductive-deductive, and Statistical Model. The techniques used were: Test of Family APGAR Smilkstein in order to know the level of functionality of these families, and Ebbe León Gross Test to assess the level of socio-emotional development of children. The main results of the Test of Family APGAR of Smilkstein were that 47% of single parent families in a group of family dysfunction, followed by a 33% functionality and un20% belonging to the group of potentially dysfunctional. Regarding test Ebbe León Gross 53% are children / as have a socio - affective satisfactory, 33% unsatisfactory present socio-emotional development, and 20% have a very satisfactory development -afectivo partner. As a final conclusion we can say that it is clear that if there is a clear impact of the dysfunction in single-parent families not optimal socio-emotional development of children of this study is given